Adaptations in driver deceleration behaviour with automatic incident detection: A naturalistic driving study. (April 2021) - Varotto, Silvia F.; Jansen, Reinier; Bijleveld, Frits; van Nes, Nicole
Highlights: Deceleration behaviour with an automatic incident detection system is analysed. The event characteristics are investigated in linear mixed-effects models. UDRIVE naturalistic driving data and a variable speed limit (VSL) database are used. Presence and visibility of the VSLs resulted in smaller maximum decelerations. Presence of the VSLs resulted in larger minimum time headways in dense traffic. Abstract: Traffic congestion and crash rates can be reduced by introducing variable speed limits (VSLs) and automatic incident detection (AID) systems. Previous findings based on loop detector measurements have revealed that drivers reduce their speeds while approaching traffic congestion when the AID system is active. Notwithstanding these behavioural effects, most microscopic traffic flow models assessing the impact of VSLs do not describe driver response accurately. This study analyses the main factors that influence driver deceleration behaviour while approaching traffic congestion with and without VSLs. The Dutch VSL database was linked to the driver behaviour data collected in the UDRIVE naturalistic driving study. Driver engagement in secondary tasks and glance behaviour were extracted from the video data. Linear mixed-effects models predicting the characteristics of deceleration events were estimated. The results show that the maximum deceleration is high when approaching a slower leader, when driving at high speeds and short distance headways, and close to the beginning of traffic congestion. The minimum time headway is short when driving at high speeds and changing lanes. Certain drivers showed higher decelerations and shorter time headways than others. Controlled for these main factors, smaller maximum decelerations were found when the VSLs were present and visible, and when the gantries were within close proximity. These factors could be incorporated into microscopic traffic simulations to evaluate the impact of AID systems on traffic congestion more realistically. Further research is needed to clarify the link between engagement in secondary tasks, glance behaviour and deceleration behaviour.